2022
DOI: 10.2147/copd.s356935
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators for Smoking Cessation in Chinese Smokers with Chronic Obstructive Pulmonary Disease: A Qualitative Study

Abstract: Background Smoking cessation is recommended as a key intervention for chronic obstructive pulmonary disease (COPD) smokers. However, in China, few COPD smokers quit successfully. The aim of this study was to explore in depth the barriers and facilitators for smoking cessation among smokers with COPD in China. Methods A purposive sample of 32 hospitalized smokers with COPD were included, 17 ex-smokers and 15 current smokers, participated in the semi-structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…For example, the physical condition of the smokers (with or without disease), the number of cigarettes smoked per day, and age may affect the effectiveness of the intervention. For example, some published studies showed that smokers with chronic obstructive pulmonary disease to have specific smoking characteristics that differentiated them from the rest of smokers and which complicated smoking cessation ( Jiménez Ruiz et al, 2012 ; Zhang et al, 2022 ). In addition, smoker’s psychological conditions or preparation may influence withdrawal, Ussher et al proposed measuring dependence and motivation of smokers to predict both short-term and medium-term outcomes of attempts to stop smoking in treatment-seeking smokers involved in a clinical trial, while Watson et al assessed the effectiveness of anxiety and depression levels in predicting smoking cessation, these attempts have shown the importance of quitting intention and psychological state of smokers ( Ussher et al, 2016 ; Watson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the physical condition of the smokers (with or without disease), the number of cigarettes smoked per day, and age may affect the effectiveness of the intervention. For example, some published studies showed that smokers with chronic obstructive pulmonary disease to have specific smoking characteristics that differentiated them from the rest of smokers and which complicated smoking cessation ( Jiménez Ruiz et al, 2012 ; Zhang et al, 2022 ). In addition, smoker’s psychological conditions or preparation may influence withdrawal, Ussher et al proposed measuring dependence and motivation of smokers to predict both short-term and medium-term outcomes of attempts to stop smoking in treatment-seeking smokers involved in a clinical trial, while Watson et al assessed the effectiveness of anxiety and depression levels in predicting smoking cessation, these attempts have shown the importance of quitting intention and psychological state of smokers ( Ussher et al, 2016 ; Watson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A promising solution could be a smartphone smoking cessation application. This technology has the potential to offer a readily accessible, costeffective, and efficient method to facilitate smoking cessation 19 and has been ardently welcomed by a significant number of Chinese smokers 9,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Nested at the core of the Behavior Change Wheel (BCW), a toolkit built for the design of behavior change strategies, the components of COM-B can be charted onto the BCW 7,8 . This can then be correlated with policy categories and intervention functions, informing the development of interventions while leveraging available resources and understanding [9][10][11] . In theory, this framework ensures a comprehensive understanding of the elements facilitating or acting as barriers to smoking cessation in China.…”
Section: Introductionmentioning
confidence: 99%
“…According to GATS China 2018, although up to 86% of people believe that smoking causes disease, and 19.8% of smokers (nearly 60 million Chinese) had tried to quit smoking in the past 12 months, the 6-month continuous abstinence rate remains very low. 6 , 10 Most ex-smokers quit smoking only by their own willpower, 11 further highlighting the need for support. Given the current situation, exploring evidence-based, effective, low-cost, and widely accessible smoking cessation services is of great practical significance.…”
Section: Introductionmentioning
confidence: 99%